Garish days - Caraganis, Lynn. (New York : WeidenFeld & Nicolson, 1988)
Louise Merrill looks back on her first trip to Paris in 1938, when she was a nineteen-year-old fashion apprentice in Columbus, Ohio.
Keywords: LIFE AND WITTY PERCEPTIONS -- FICTION